Supercritical fluid extraction of polyphenols from lees: overall extraction curve, kinetic data and composition of the extracts - Angela M. Farías-Campomanes; Maurı́cio A. Rostagno; Joel Jerson Coaquira-Quispe; M. Ângela A. Meireles (My University, 2015)
The increasing incidence of degenerative diseases has attracted the interest in the obtaining of bioactive compounds. Since seeds and skins from grapes are important sources of polyphenols which have been associated with cancer incidence decreasing, then, one of the pisco (alcoholic beverage made of grape) manufacturing byproduct such as lees, could be a potential source of polyphenols. Supercritical fluid extraction is an environmentally friendly technique that has been applied for obtaining polyphenols. Carbon dioxide is used as unique or main extraction solvent instead of organic solvents, most of them toxics and responsible for reducing the application fields of the extracts. For that reason, among others, supercritical fluid extraction is preferred over conventional techniques for obtaining bioactive compounds. The aim of this work was to study the supercritical fluid extraction of polyphenols from lees of pisco-making. Supercritical carbon dioxide with 10 % of ethanol (w/w) was used as extraction solvent. Overall extraction curves were determined at 20 and 35 MPa; and the experimental data were used to estimate the kinetic parameters. Conventional techniques using ethanol as extraction solvent were performed for comparative purposes. The extracts were analyzed by thin-layer and high-performance liquid chromatography. Lower global yield was obtained by supercritical fluid extraction than conventional techniques. From the kinetic parameters, the mass transfer rate and the amount of the extract dissolved in supercritical phase were higher at 20 than 35 MPa. Phenolic acids (gallic, protocatechuic, vanillic, syringic, ferulic derivatives and p-coumaric derivatives) and flavonoids (quercetin and its derivatives) were identified in the extracts obtained by all extraction techniques. Polyphenols were rapidly extracted with supercritical fluid and more concentrated extracts were obtained at 20 MPa. However, for longer extraction times, the highest values of extracted polyphenols were obtained by conventional techniques. Lees from pisco-making are a promising source for recovery polyphenols. Low global yields were obtained when elevated pressures were used. Although supercritical fluid extraction at 20 MPa was the most efficient technique on the extraction of polyphenols from lees of pisco-making due to highly concentrated polyphenols, extracts were rapidly obtained.
Keywords: Supercritical fluid extraction; Supercritical fluid; Chromatography; Polyphenol; Chemistry; Extraction (chemistry); Supercritical carbon dioxide; Lees; Vanillic acid; Solvent; Organic chemistry; Fermentation; Antioxidant; Supercritical fluid extraction; Supercritical fluid; Chromatography; Polyphenol; Chemistry; Extraction (chemistry); Supercritical carbon dioxide; Lees; Vanillic acid; Solvent; Organic chemistry; Fermentation; Physical Sciences Engineering Biomedical Engineering Phase Equilibria and Thermodynamics; Health Sciences Medicine Biochemistry Phytochemicals and Antioxidant Activities; Physical Sciences Chemistry Spectroscopy Analytical Chemistry and Chromatography